Market Reaction To The Publication Of Key Audit Matters (KAMs) - Atina Karima (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2025)
Auditing Standard (SA) 701 establishes the auditor's responsibility to communicate Key Audit Matters (KAMs) in the independent auditor’s report. This study aims to analyze the market reaction to the publication of Key Audit Matters, as measured by Abnormal Return (AR) and Trading Volume Activity (TVA). The research employs an event study method with a one-sample t-test, observing a window of five days before and after the KAMs announcement. The sample was selected randomly using simple random sampling and the Slovin formula, comprising 280 companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period, with a total of 450 audited financial reports observed. Based on Signalling Theory, the researcher categorized KAMs into three types based on their informational content: KAMs disclosing positive information, KAMs disclosing negative information, and KAMs disclosing non-value-added information to the market. The results indicate a positive market reaction to the publication of KAMs containing positive information, a negative market reaction to those containing negative information, and no significant market reaction to KAMs that provide no added informational value.